Influence of Alkoxy Chain Length on the Initiating Efficiencies of Tributyltin(IV) Alkoxides in the Ring-opening Polymerizations of L-Lactide and ε-Caprolactone - Wanich Limwanich (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The kinetics of the ring-opening polymerizations (ROP) of L-lactide (LL) and ε-caprolactone (ε-CL) initiated by the synthesized tributyltin(IV) alkoxides (nBu3SnOR; R = Me, Et, nPr and nBu) was firstly investigated by means of non-isothermal differential scanning calorimetry (DSC) and proton nuclear magnetic resonance spectroscopy (1H-NMR) techniques. The nBu3SnOR initiators were synthesized from nucleophilic substitution of tributyltin chloride (nBu3SnCl) by sodium alkoxides (NaOR; R = Me, Et, nPr and nBu). The %yield of nBu3SnOR initiators was higher than 60%. These initiators were completely soluble in common organic solvents. From non-isothermal DSC kinetics analysis, the polymerization rate (dα/dt) increased with increasing heating rates and nBu3SnOnBu concentrations. The activation energies (Ea) were rapidly determined by Kissinger and Ozawa methods. Furthermore, the dependency of Eawith monomer conversion was also investigated by Friedman and Kissinger-Akahira-Sunose (KAS) isoconverisonal methods. The Ea values decreased with increasing initiator concentrations but increased with alkoxy chain length of initiator. From 1H-NMR analysis, the Ea values decreased with increasing initiator concentrations which were similar to DSC technique. The values of Ea obtained from 1H-NMR were higher than DSC technique. From the results obtained from both methods, the reactivity of nBu3SnOR initiators was in the following order: nBu3SnOMe > nBu3SnOEt > nBu3SnOnPr > nBu3SnOnBu. The polymerization mechanism of all systems was proposed through the coordination-insertion mechanism which was confirmed by 1H-NMR technique. The efficiency of the nBu3SnOR initiators in the synthesis of poly(L-lactide) (PLL) and poly(-caprolactone) (PCL) was studied by bulk polymerization of LL and ε-CL conducted at 120ºC for 72 h. The molecular weight of PLL and PCL was controlled by initiator concentration used. It was important to note that the nBu3SnOnBu produced the highest molecular weight and %yield of PLL and PCL. Furthermore, the molecular weight of PLL and PCL increased with increasing alkoxy chain length of initiator. The molecular weight distribution (MWD) of all synthesized polymers were lower than 2.1. From carbon-13 nuclear magnetic resonance spectroscopy (13C-NMR) analysis, the racemization of PLL was not observed for all initiators. From thermal characterization, the melting temperatures of the synthesized PLL and PCL were in the range of 160.0-170.0°C and 53.8-58.1°C, respectively. The percentage relative crystallinity (%Xc) of the synthesized PLL and PCL were 46.5-80.3% and 44.7-63.9%, respectively. From the experimental point of view it should be noted that the DSC is a fast, convenient and reliable method for studying the kinetics of ROP of cyclic ester monomers.